Rancang Bangun Alat Bantu Pemasangan Metal Clip Terhadap Holder Plastik Dengan Menggunakan Sistem Pneumatik - Dodi Mulyadi; Nova Ardianto; Amir Amir; Karyadi Karyadi; Khoirudin Khoirudin (Universitas Muhammadiyah Metro, 2026)
Jig is a special tool that designed to hold, guide, and maintain the stability of a workpiece during the manufacturing process. In this study, the jig was used to hold a plastic holder so that it would not shift when a metal clip was pressed or installed. The use of a jig is expected to improve the work process efficiency and consistency.The objective of this study was to design and manufacture a pneumatic-based press jig for installing metal clips on a plastic holder. This design was developed through a calculation and construction process for optimal application in the production process. FluidSIM software was used to simulate the pneumatic wiring in the pneumatic system. This simulation helps ensure that the pneumatic circuit functions properly and serves as the primary reference for designing the pneumatic wiring in the press jig. The results showed that the press jig was successfully manufactured and operated satisfactorily. Air pressure was set as 0.2 MPa with variable speed control proved to be ideal and optimal. These conditions resulted in a product without defects and could be applied in production processes requiring high quality standards.